2005
DOI: 10.1097/00001665-200503000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Adjunctive Benefits of Platelet-Rich Plasma in Subantral Sinus Augmentation

Abstract: Subantral sinus augmentation is often necessary to permit placement of endosseous implants. Recent efforts to improve wound healing have focused on autogenous sources of bioactive mediators, such as platelet-rich plasma (PRP), which offer the potential to enhance the biological activity of bone replacement grafts. The purpose of this randomized, single-blinded, controlled study was to compare bone formation after subantral maxillary sinus augmentation with freeze-dried bone allograft (FDBA) plus PRP versus FDB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
93
0
7

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 20 publications
0
93
0
7
Order By: Relevance
“…However, some complications such as ecchymosis, hematomas and infections may occur after fat grafting. Specifically, the unexpected and low survival rate (approximately 20-80 %) is a common and important issue [2,3]. To solve the problem of traditional fat grafting, surgeons have begun to use cell-assisted lipotransfer (CAL), whereby adipose-derived stem cells (ASCs) are cotransplanted with fat grafts.…”
Section: Introductionmentioning
confidence: 99%
“…However, some complications such as ecchymosis, hematomas and infections may occur after fat grafting. Specifically, the unexpected and low survival rate (approximately 20-80 %) is a common and important issue [2,3]. To solve the problem of traditional fat grafting, surgeons have begun to use cell-assisted lipotransfer (CAL), whereby adipose-derived stem cells (ASCs) are cotransplanted with fat grafts.…”
Section: Introductionmentioning
confidence: 99%
“…All these approaches are known as regenerative therapies. Recently it has been developed a procedure for bony defects regeneration utilizes PRP in addition to bone grafts, and several studies have showed that a combination of PRP with bone grafts promote bone regeneration [36][37][38][39][40][41][42]. However, other authors still argue the lack of scientific evidence for defending the use of PRP associated with bone grafts in bone regeneration and recommend the surgeon to maintain a critical mind regarding its efficacy [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Although many controversial results are reported, PRP is also widely used in the field of bone tissue engineering. Clinical studies by Marx et al (1998) and Oyama et al (2004) in the field of oral-maxillofacial reconstructions showed a strong effect of PRP on bone formation (88 and 12 patients, respectively), while there was weak to absent effect on bone formation in other studies investigating 26 and 10 patients (Dori et al, 2008;Kassolis and Reynolds, 2005).…”
Section: Clinical Use Of Prpmentioning
confidence: 93%